Snake eels of the genus Ophichthus (Anguilliformes: Ophichthidae) from Myanmar (Indian Ocean) with the description of two new species - Mccosker, John E.; Psomadakis, Peter N. (Zootaxa, 2018)
Two new species of ophichthid eels, subfamily Ophichthinae, are described and illustrated from specimens collected from Myanmar by the R/V Dr. Fridtjof Nansen. Included are: Ophichthus nansen sp. nov., from 103–106 m depth, which is unique in its vertebral number (11-53-116), dorsal-fin origin (above mid-pectoral fin), jaw dentition (small, conical and mostly biserial), and coloration (dark gray-brown, fins black); and Ophichthus naga sp. nov., from 455–459 m depth, which is unique in its vertebral number (15-65-153), dorsal-fin origin (well behind pectoral fin), dentition (small, conical, biserial in upper jaw and uniserial in lower jaw and on vomer), and dark brown coloration. Also new to Myanmar are Ophichthus cephalozona Bleeker, 1864, and O. lithinus (Jordan & Richardson, 1908), which are diagnosed and treated herein.